Application of video analytics to monitor and improve the safety of technological processes - Konstantin V. Chumakov (Известия Томского политехнического университета: Промышленная кибернетика)
The article presents the results of using video analytics based on artificial intelligence and computer vision algorithms to monitor compliance with safety rules during production work, as well as to monitor emergency situations. The author has developed the approach that allows real-time detection of non-standard events and prevention of potential emergency situations. The paper describes the key artificial intelligence algorithms used to process and interpret the video data stream.